Polymorphisms in the T cell regulatory gene cytotoxic T lymphocyte antigen 4 influence the rate of acute rejection after liver transplantation. Issue 6 (18th November 2005) - Tapirdamaz, Ö; Pravica, V; Metselaar, H J; Hansen, B; Moons, L; van Meurs, J B J; Hutchinson, I V; Shaw, J; Agarwal, K; Adams, D H; Day, C P; Kwekkeboom, J
Abstract : Background: The cytotoxic T lymphocyte antigen 4 (CTLA-4) gene encodes for a membrane bound (mCTLA-4) and a soluble (sCTLA-4) isoform, which are both involved in regulation of T cell function. The CTLA-4 +49A/G single nucleotide polymorphism (SNP) influences expression of mCTLA-4; +6230G/A SNP affects the production of sCTLA-4. Aim: To examine whether these functional SNPs influence the rate of rejection after liver transplantation. Patients and methods: Liver graft recipients (n = 483) were genotyped for both SNPs, and haplotypes were reconstructed. Association with rejection was tested by the log rank test using the Kaplan-Meier method with time to the first acute rejection episode as outcome. Multiple analysis of SNPs together with demographic factors was performed by Cox regression. Results: Three haplotypes were observed in the cohort: +49A/+6230A, +49A/+6230G, and +49G/+6230G. The +49A/+6230G haplotype was significantly and dose dependently associated with acute rejection (p = 0.01). Of the demographic factors tested, only underlying liver disease was significantly associated with rejection. Adjusted for underlying liver disease, each additional +49A/+6230G haplotype allele resulted in a significantly higher risk of acute rejection (risk ratio 1.34 (95% confidence interval 1.04–1.72); p = 0.02). Patients who lacked this haplotype had the lowest, carriers an intermediate, and homozygotes the highest risk of acute rejection. Conclusion: The CTLA-4 +49A/+6230G haplotype, which encodes for normal mCTLA-4 expression but reduced sCTLA-4 production, is a co-dominant risk allele for acute rejection after clinical liver transplantation. This implies that even under immunosuppression, CTLA-4 is critically involved in the regulation of the human immune response to allogeneic grafts.